The movement of the rider’s hand related to the horse’s behaviour and the stride cycle - Eisersiö, Marie (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2012)
One way of signalling commands to the horse during riding is through applying tension on the reins to create bit pressure in the horse‟s mouth (Terada et al., 2006; Clayton et al., 2011). The skilfulness of the rider in using the hands when applying bit pressure has consequences both for the horse‟s performance and welfare (Manfredi et al., 2010). At the trot there are large vertical deviations of the horse‟s body which the rider must adjust and adapt to (Terada et al., 2006) and an unsteady hand due to inability to follow the horse‟s movement can be a source of discomfort and conflict behaviour in the horse (Heleski et al., 2009). By examining the rider‟s signals and the horse‟s behavioural expression, clues can be received about the horse‟s experience of its training. The aim of this project was to describe the rider‟s hand movement and the horse‟s head movement during sitting trot and to find relationships between these variables, the horse‟s behaviour, the rein tension and the stride cycle. The hypothesis was that the rider‟s hand will interact with the horse through the reins in a regular pattern correlated to the horse‟s head movement and stride cycle and that the horse will show behavioural responses to these interactions. Seven dressage horses were ridden in trot on a treadmill with an integrated force measuring system and infrared cameras registering the position of reflective markers on the horse‟s head and the rider‟s hands. Three horses wore a rein tension meter and all horses were studied for behavioural responses. Behavioural responses included changes in head-, ear- and tail position as well as gestures with the mouth. Ground reaction forces (GRF) were used to define the stride cycle. All data were normalised into 101 data points, 0-100 % of a stride cycle. From the normalised stride curves, range of motion, mean values and variation were calculated. The kinematic, behavioural and rein tension data were related to the stride cycle and examined for their general activity. The rider‟s hand movement and the horse‟s head movement followed the same movement pattern in the X- and Z-axis. Increased proportion of mouth behaviours, increased distance between the rider‟s hand and the horse‟s head as well as increased rein tension were all associated with the suspension phase at the trot. Behavioural registration combined with biomechanical measurement yields information about the horse‟s response to rider actions and is beneficial when evaluating training techniques and rider performance.